Efficient C–C coupling of bio-based furanics and carbonyl compounds to liquid hydrocarbon precursors over lignosulfonate derived acidic carbocatalysts. Issue 9 (18th April 2018) - Konwar, Lakhya Jyoti; Samikannu, Ajaikumar; Mäki-Arvela, Päivi; Mikkola, Jyri-Pekka
Abstract : Synthesis of jet fuel (branched hydrocarbon) precursors from bio based furanics and carbonyls over highly stable, active acidic carbocatalysts derived from Na-lignosulfonate. Abstract : This paper demonstrates the catalytic potential of novel Na-lignosulfonate (LS) derived meso/macroporous solid protonic acids upon C–C coupling of bio-based furanics and carbonyl compounds. The materials demonstrated catalytic activity for solventless hydroxyalkylation/alkylation (HAA) of 2-methylfuran with furfural, acetone, butanal, cyclohexanone, levulinic acid and α-angelica lactone under mild reaction conditions (50–60 °C) producing branched-chain C12–C16 hydrocarbon precursors in yields approaching 96%. Moreover, the carbon materials exhibiting high total acidity (6–6.4 mmol g −1 ) outperformed sulfonic acid resins (Amberlyst®70, Amberlite®IR120 and LS resin), zeolites and liquid acids ( p -toluenesulfonic acid, acetic acid and phenol). In fact, the most active carbocatalyst (60LS40PS350H + ) exhibited the same turnover frequency as p -toluenesulfonic acid (186 h −1 ) upon furfural conversion but with an improved HAA product yield (up to 88%) and reusability, maintaining 98% of its original activity up to seven reaction cycles. The observed catalytic activity and operational stability of the LS derived acidic carbocatalysts were attributed to the strongly Brønsted acidic –SO3 H groups covalently incorporated into their structural carbon framework and the promotional effects of hydrophilic surface functional groups (–COOH and –OH) favoring adsorption of oxygenated reactant molecules.